Aspek Insentif, Mekanisme Pengambilan Keputusan dan Koordinasi (Analisis Komparasi Sistem-Sistem Ekonomi) - Nafis Irkhami (Muqtasid: Jurnal Ekonomi dan Perbankan Syariah, 2015)
This paper is intended as a general comparative study on the economic system of capitalism, socialism and Islamic economics. The comparative analysis is conducted by reviewing aspects of incentives, decision-making mechanism and coordination. Inter-systemic review in this paper shows that Islamic economic system is determined by the parameters of its own ethical system which shows originality and relativity. Unlike other systems, the ethical impulse that is based on the Islamic worldview is fully integrated with Islamic economic motives. Limited freedom assigned to the behavior of consumption and production, as well as the emphasis on the distribution of wealth cannot be separated from the purpose of goodness (world and the hereafter).Tulisan ini dimaksudkan sebagai studi komparasi general atas sistem ekonomikapitalisme, sosialisme (ekonomi komando) dan ekonomi Islam. Analisiskomparasi tersebut dilakukan dengan meninjau aspe-aspek insentif, mekanismepengambilan keputusan dan koordinasi. Tinjauan inter-sistemik dalam tulisanini menunjukkan bahwa sistem ekonomi Islam ditentukan berdasarkan parameter-parameter sistem etisnya sendiri, yang menunjukkan adanya orisinalitas dan relativitasnya. Tidak seperti sistem lain, impuls-impuls etik yang didasarkan pada worldview Islam tersebut sepenuhnya terintegrasi dengan motif-motif ekonomi Islam. Kebebasan terbatas yang ditetapkan untuk perilaku konsumsi dan produksi, serta penekanan pada distribusi kekayaan tidak dapat dipisahkan dari tujuan kemaslahatan (dunia maupun akhirat).